Preferential assimilation of NH4+ over NO3− in tea plant associated with genes involved in nitrogen transportation, utilization and catechins biosynthesis. (February 2020) - Tang, Dandan; Liu, Mei-Ya; Zhang, Qunfeng; Ma, Lifeng; Shi, Yuanzhi; Ruan, Jianyun
Highlights: 15 NH4 + -fed tea plants accumulate more 15 N than 15 NO3 − -fed plants. Tea plants maintain a balanced concentration of NH4 + in tea leaves. Genes involved in primary N assimilation is related to the lower assimilation of NO3 − -than NH4 + . Balancing of NH4 + in tea leaves was obtained through theanine and catechins metabolism. Abstract: Physiological effects of ammonium (NH4 + ) and nitrate (NO3 − ) on tea have confirmed that tea plants prefer NH4 + as the dominant nitrogen (N) source. To investigate the possible explanations for this preference, studies of 15 NH4 + and 15 NO3 − assimilation using hydroponically grown tea plants were conducted. During the time course of 15 NH4 + and 15 NO3 − assimilation, the absorption of 15 N from 15 NH4 + was more rapid than that from 15 NO3 −, as there was a more efficient expression pattern of NH4 + transporters compared with that of NO3 − transporters. 15 NH4 + -fed tea plants accumulated more 15 N than 15 NO3 − fed plants, which was demonstrated by that genes related to primary N assimilation, like CsNR, CsNiR, CsGDH and CsGOGAT, were more affected by 15 NH4 + than 15 NO3 − . Markedly higher NH4 + concentrations were observed in 15 NH4 + -fed tea roots in comparison with NO3 − treatment, whereas tea plants maintained a balanced concentration of NH4 + in tea leaves under both these two N forms. This maintenance was achieved through the increased expression of genes involved in theanine biosynthesis and the inhibition of genes related to catechins derived from phenylpropanoid pathway. The current results suggest that efficient NH4 + transportation, assimilation, and reutilization enables tea plant as an ammonium preferring plant species.